Proximal tibial metaphyseal fractures in immature dogs - Deahl, Lauren; Ben-Amotz, Ron; Caceres, Ana V.; Agnello, Kimberly A. (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Objective: To describe proximal tibial metaphyseal fractures in immature dogs.Materials and methods: Medical records of immature dogs with metaphyseal fractures of the proximal tibia were reviewed and data were collected on signalment and history of trauma. Craniocaudal and mediolateral radiographs were evaluated for the determination of the bones fractured, location of the fracture within the bone, fracture configuration, and the presence of fracture segment displacement and angulation.Results: Eighteen dogs with 22 proximal tibial metaphyseal fractures fulfilled the inclusion criteria. All fractures had a curvilinear, complete fracture of the proximal tibial metaphysis. Displacement was identified in 16 fractures and angulation in 15 fractures. All affected breeds were terrier or small breed dogs less than six months of age. The majority of dogs weighed 5 kg or less at the time of injury. The most common type of trauma that occurred was a jump or fall from a short distance.Clinical significance: Proximal tibial metaphyseal fractures are an uncommon injury that occur in skeletally immature dogs from minimal trauma. Proximal tibial metaphyseal fractures have a characteristic curvilinear fracture configuration that affects mainly small breed dogs with a predominance for terrier breeds.Supplementary Material to this article is available online at https://doi.org/10.3415/VCOT-16-11-0154
Keywords: Metaphyseal fracture; tibia fracture; canine; immature